Modified triple assessment in the diagnosis of breast lump in Saurashtra region of Gujarat - Solanki, Pradipkumar V.; Juneja, Iliyas A.; Chaudhari, Nileshbhai D. (International Surgery Journal, 2020)
Background: Breast lump is a common complaint of women presenting to surgeons. Most of them are benign, careful evaluation, exact diagnosis and definitive treatment is mandatory to rule out cancer. The diagnosis of breast cancer is suggested on clinical examination. Currently a combination of three tests, i.e. clinical examination, radiological imaging (mammography, ultrasonography) and pathology called as triple assessment test is used to accurately diagnose all palpable breast lumps. Together they give sensitivity of 100%. The triple assessment is taken as positive if any of the three components, two are positive or positive report of FNAC and negative only if all of its components are negative for malignancy. Methods: This study was conducted in the Department of Surgery, P.D.U Medical College, Rajkot, Gujarat over a period of 2 years. A total of 100 patients with a breast lump were selected more than 15 years of age. A detailed history, focused clinical examination, radiological imaging and FNAC were used as diagnostic tools for screening of the patients. The aim of this study was to evaluate accuracy of modified triple assessment in the preoperative diagnosis of patients with breast carcinoma. Results: Results shows sensitivity and specificity of all the modalities used in triple assessment when combined together was 100% and 99.3%, respectively. Positive predictive value was 93.3%, negative predictive value was 100%, p-value was highly significant (p<0.0001). We conclude that modified triple assessment is a very useful diagnostic tool to evaluate patients with breast lumps and an overall accuracy of 98%. Conclusions: Thus, triple assessment is an easily available, cost effective, least invasive, rapid and patient compliant diagnostic tool for diagnosis of breast lump.